RISIKO KREDIT, RISIKO LIKUIDITAS, RISIKO OPERASIONAL DAN PROFITABILITAS - Gayatri, Ni Wayan Pebry Diyan; Mahaputra, I Nyoman Kusuma Adnyana; Sunarwijaya, I Ketut (Jurnal Riset Akuntansi (JUARA), 2019)
Bank Perkreditan Rakyat (BPR) is a bank whose role is to collect and channel funds.Banks that carry out business activities conventionally or based on sharia principles which intheir activities do not provide services in payment traffic. Several studies on the effect of thelevel of credit risk (NPL), liquidity risk (LDR), operational risk (BOPO) on profitability (ROA) havebeen carried out. However, the results of these studies still show inconsistency. This study aimsto reexamine the influence of the level of credit risk (NPL), liquidity risk (LDR) and operationalrisk (BOPO) on profitability (ROA).This research was conducted at the Bank Perkreditan Rakyat in Gianyar district in2015-2017. The sampling technique used was purposive sampling technique. The sample inthis study amounted to 22 People’s Credit Banks with a total of 66 observations. Data analysistechniques used multiple linear regression analysis.The results showed that credit risk (NPL) and liquidity risk (LDR) had no effect on profitabilityBPR in Gianyar Regency 2015-2017 while operational risk (BOPO) negatively affectedprofitability BPR in Gianyar Regency 2015-2017 so the research hypothesis this is accepted.